2000
DOI: 10.1001/archotol.126.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Vascular Invasion in Papillary Thyroid Carcinoma

Abstract: These associations were found to be independent by multiple regression analysis. Patient age, sex, palpable or fixed lymph nodes, radiation exposure, and race did not differ between the patient group with and those without vascular invasion. Preliminary analysis of our data suggests that the presence of vascular invasion in papillary, thyroid carcinoma, even within the thyroid gland, is associated with more aggressive disease at diagnosis and with a higher incidence of tumor recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 17 publications
10
60
1
3
Order By: Relevance
“…On the contrary, more than 4 foci of vascular invasion are associated with a poor prognosis, mainly in follicular carcinomas (30)(31)(32). This situation seems to be uncommon in papillary carcinomas, even more in micro PTC, with a prevalence of less than 4% (25,26,28,(33)(34)(35). In fact, none of the 63 patients from our cohort had vascular invasion in more than 4 foci in the pathological review.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…On the contrary, more than 4 foci of vascular invasion are associated with a poor prognosis, mainly in follicular carcinomas (30)(31)(32). This situation seems to be uncommon in papillary carcinomas, even more in micro PTC, with a prevalence of less than 4% (25,26,28,(33)(34)(35). In fact, none of the 63 patients from our cohort had vascular invasion in more than 4 foci in the pathological review.…”
Section: Resultsmentioning
confidence: 59%
“…The presence of vascular invasion is recognized as a variable that has a negative impact on the RR (25)(26)(27), and it should be informed in the pathological report. It is diagnosed as a direct tumor extension into the blood vessel lumen typically attached to the wall and covered by a fibrin thrombus (27).…”
Section: Resultsmentioning
confidence: 99%
“…29,30 In our study, higher MVD, as an indicator of the extent of angiogenesis, was strongly associated with the presence of vascular invasion. Histologically determined vascular invasion may be considered a sign of a greater tendency toward hematogenous spread of tumor cells and could result in increased formation of metastases.…”
Section: 7supporting
confidence: 54%
“…[10][11][12][13][31][32][33] Nishida et al 33 reported vascular invasion in 46.9% of papillary thyroid carcinomas and distant metastases in only 8% of angioinvasive papillary thyroid carcinomas, suggesting that the criteria applied were not specific enough to identify high risk patients. Our review identified rigid criteria of vascular invasion in only 3% of thyroid carcinomas.…”
Section: Discussionmentioning
confidence: 99%